(untitled) (Research, Society and Development, 2021)
This study sought to assess the bacterial profile involved in Foodborne Diseases (FED) in the Northeast region of Brazil for the year 2019, and also to identify which states in this region had the highest number of notifications for DTA, as well as to investigate the places and foods where these outbreaks occur most frequently. This is a descriptive study with a qualitative approach and data from the Information System for Notifiable Diseases (SINAN) was used, this information was organized in tables and then content analysis was performed. The results showed that the bacterial strains most identified in the outbreaks were: Escherichia coli (62%), Staphylococcus aureus (14%) and Salmonela (7%) and the state of the Northeast region, where the highest number of outbreaks was recorded was Pernambuco (82%), the place with the highest incidence of contamination was homes (60%) and water (62%) was identified as the main vehicle of contamination. Therefore, the information obtained in this research can support the adoption of necessary policies for the control of these diseases in the Northeast region, and the promotion of greater investments in educational and legislative actions, and that work like this involving other regions would be extremely relevant , because that way it would be possible to verify the reality of each region of Brazil.